(untitled) (REMUNOM, 2026)
Quantitative, retrospective, and descriptive-analytical study, conducted using secondary data from the Brazilian Notifiable Diseases Information System (SINAN), aiming to analyze tuberculosis treatment abandonment in Brazil from 2026 to 2024. Among the analyzed cases, the category new case predominated (64.0%), followed by re-entry after abandonment (26.4%), which was considered a key category due to the high recurrence of the outcome. A higher prevalence of treatment abandonment was observed among individuals who did not undergo Directly Observed Treatment (DOT), with a proportion of 20.1%, compared to those who received DOT (8.6%), yielding a prevalence ratio of 2.34 (95% CI: 2.31–2.38; p<0.001). Analysis of vulnerability conditions showed a higher prevalence of abandonment among the homeless population (PR=2.94; 95% CI: 2.87–3.01), illicit drug users (PR=2.59; 95% CI: 2.55–2.63), individuals with alcoholism (PR=1.95; 95% CI: 1.92–1.98), and people living with HIV (PR=1.83; 95% CI: 1.80–1.86). In contrast, the incarcerated population showed a lower prevalence of treatment abandonment (PR=0.71; 95% CI: 0.70–0.73). These findings reinforce treatment abandonment as a phenomenon strongly associated with social vulnerability and the absence of effective follow-up strategies, highlighting the importance of strengthening DOT and intersectoral actions to reduce this outcome.